Association between the Increasing Dose or Number of Antihypertensive Drugs and the Control of Hypertension in the Hypertensive Patients at Sam Liam Primary Care Unit, Muang District, Khon Kaen Province - Ruedech, Pakorn; Whasuwan, Thanapat; Jessadapattarakul, Sirawit; Kamolwat, Kanokporn; Mongkolsangsuree, Thanawan; Ketsomboon, Pattapong; Jodking, Prompisit (Srinagarind Medical Journal, 2018)
Background and Objectives : Hypertension is an important disease that about 40% of patients have uncontrolled outcome leading to complications and deaths. Increasing doses or number of drugs were usually performed by doctors in patients with uncontrolled hypertension. The purpose of this study was to determine the association between the increasing doses or number of drugs and the control of hypertension and also association between factors and target organ damage. Methods : This was a retrospective cohort study. The number of hypertensive patients in Sam Liam community was 1,076 and 220 patients were simple random sampling into this study. Data was collected by using the record form and reviewing the information from OPD card and database at Sam Liam primary care unit. Data analysis was conducted and presented by frequency, proportion, percentage, mean, median, standard deviation, interquartile range, 95% confidence interval, relative risk, and adjusted Odds ratio. Results : From 220 patients, the number of patients with controlled hypertension was 132 (60 %). Increasing of drug was statistically significantly associated with the control of hypertension (RR 1.41, 95%CI : 1.13-1.77). Furthermore, no dyslipidemia (RR 0.52, 95%CI : 0.29-0.96) and not having other comorbidities (RR 0.45, 95%CI : 0.25-0.83) were statistically significantly associated with target organ damage. Also, serum potassium was statistically significantly associated with target organ damage (p=0.04). Conclusion : Increasing of drug results in controlled hypertension by 1.41 times better than non-increasing of drug.